Torn Between Two Plates: Exhumation of the Cer Massif (Internal Dinarides) as a Far‐Field Effect of Carpathian Slab Rollback Inferred From 40Ar/39Ar Dating and Cross Section Balancing. Issue 6 (7th June 2021) - Löwe, Georg; Schneider, Susanne; Sperner, Blanka; Balling, Philipp; Pfänder, Jörg A.; Ustaszewski, Kamil
Abstract: Extension across the southern Pannonian Basin and the internal Dinarides is characterized by Oligo‐Miocene metamorphic core complexes (MCCs) exhumed along mylonitic low‐angle extensional shear zones. Cer MCC at the transition between Dinarides and Pannonian Basin occupies a structural position within the distal‐most Adriatic thrust sheet and originates from two different tectonic processes: Late Cretaceous‐Paleogene nappe‐stacking during a continent‐continent collision with Adria in a lower plate position, and exhumation related to Miocene extension driven by the Carpathian slab‐rollback. Structural data and a balanced cross section across the Cer massif show linking of the exhuming shear zone to a breakaway fault, which reactivated the early Late Cretaceous most internal nappe contact. Paleozoic greenschist‐to amphibolite‐grade lithologies surround a polyphase intrusion composed of I‐ and S‐type granites and were exhumed along a shear zone characterized by top‐N transport. Thermobarometric analyses indicate an intrusion depth of 7–8 km of the Oligocene I‐type granite; cooling below ∼500°C occurred at 25.4 ± 0.6 Ma (1σ) yielded by 40 Ar/ 39 Ar dating of hornblende. Biotite and white mica from this intrusion as well as from the mylonitic shear zone yield 40 Ar/ 39 Ar cooling ages of 17–18 Ma independent of the used techniques (in situ laser ablation, single‐grain total fusion, single‐grain step heating, and multi‐grain step heating). White mica from the S‐type granite yield an 40 Ar/ 39 Ar cooling age of 16.7 ± 0.1 Ma (1σ). Associated dikes intruding the shear zone were also affected by N‐S extension resulting in the exhumation of the MCC, which was triggered by the opening of the Pannonian back‐arc basin in response to the Carpathian slab‐rollback. Plain Language Summary: Horizontal stretching of continental plates induces thinning of the crustal upper part, melting of rocks, the sinking of the land surface, and formation of large basins. One of the world's best‐studied basins formed by such a process is the Central European Pannonian Basin. This basin is surrounded by the mountain belts of the Alps, Carpathians, and Dinarides. We have studied rocks between the Pannonian Basin and the southerly adjacent Dinaride Mountains, where rocks deposited in the basin are found right next to rocks that were initially about 7–8 km deep in the crust. These rocks are separated by a shear zone, along which they were brought to the surface. We have dated the activity of the shear zone by measuring concentrations of radioactive isotopes and their decay products contained in deformed minerals. The shear zone was active at a time when the Pannonian Basin started to open due to tectonic processes further NE underneath the Carpathian mountain chain. We also found evidence that the shear zone, which brought metamorphic rocks upwards was formerly one that brought rocks downwards into the crust during an earlier phase of mountain building, predating basin formation. Key Points: Activity along the shear zone exhuming Cer metamorphic core complex in the internal Dinarides was dated by 40 Ar/ 39 Ar geochronology to ∼17 Ma Exhumation was facilitated by extensional reactivation of Late Cretaceous‐Paleogene nappe contacts resulting from Adria‐Europe collision Extensional reactivation of the thrusts is interpreted as a far‐field effect of Oligo‐Miocene Carpathian slab rollback